Anterior and posterior neck muscle activation during a variety of biting tasks - Hellmann, Daniel; Giannakopoulos, Nikolaos Nikitas; Schmitter, Marc; Schindler, Hans J. (European journal of oral sciences, 2012)
Bruxism may be involved in the aetiology of myofascial neck pain. The objective of this study was to test the hypothesis that anterior and posterior neck muscles co-contract during jaw clenching. Ten test subjects developed different feedback-controlled submaximum bite forces in a variety of bite-force directions by means of bite-force transducers. The electromyographic activity of the sternocleidomastoid and supra/infrahyoidal muscles, and of the semispinalis capitis, semispinalis cervicis, and multifidi muscles was recorded by use of surface electrodes and intramuscular wire electrodes, respectively. For normalization of electromyography data, maximum voluntary contraction tasks of the neck muscles were conducted in eight different loading directions. The results confirmed co-contraction of the neck muscles in the range of 2-14% of the maximum voluntary contraction at a bite force ranging from 50 to 300 N. Significant activity differences were observed as a result of the different force levels and force directions exerted by the jaw muscles. Long-lasting tonic activation of specific neck muscles triggered by the jaw-clenching tasks was also detected. These findings support the assumption of a relationship between jaw clenching and the activity of the neck muscles investigated. The low level of co-contraction activity, however, requires further study to elucidate possible pathophysiological interactions at the level of single motor units.
Gesehen am 25.04.2018